E-235 Use of 45 mg twice daily ticagrelor with 81 mg aspirin for endovascular treatment of unruptured intracranial aneurysms: a single center experience. (4th August 2020) - Mehta, T; Masood, K; Ghannnam, M; Grande, A; Tummala, R; Jagadeesan, B
Abstract : Introduction: Stent assisted coiling (SAC) and Flow diverter (FD) placement are commonly used techniques for the treatment of unruptured intracranial aneurysms (UIA). Stents and FDs require dual antiplatelet therapy (DAPT ) to prevent in-stent thrombosis. The selection of medications is mainly operator dependent. Cardiovascular literature suggests that the use of Aspirin 81 mg in conjunction with low dose Ticagrelor (45 mg twice daily) is superior than the use of Clopidogrel 75 mg and Aspiring 325 mg. Methods: We performed a retrospective chart review of patients who underwent treatment of UIA at our institution using SAC or FD from 2016–2019. The patients who are on anticoagulation or did not have a pre-procedure P2Y12 inhibition assay were excluded. The patient group receiving Brilinta 45 mg twice daily with aspirin 81 mg daily (Group 1) was compared with the patient group receiving Plavix 75 mg daily with aspirin 325 mg daily (Group 2). The primary outcome was defined as intraoperative or acute (during hospitalization) postoperative stroke. Secondary outcomes included ischemic stroke after discharge within one year from treatment, and differences in P2Y12 inhibition assay values between the two groups. Results: A total of 111 patients were identified that met the inclusion criteria, 42 (37.8%) in Group 1, and 69 in Group 2 (62.2%) protocol. There was no significant difference in the primary outcome between the two groups; Group 1, (2 patients, 4.7%), and Group 2 (1 patient, 1.4%) (p=0.11). All the primary end point events in both groups were related to FD. Clinically significant ischemic stroke after discharge within one year was also not significantly different (2 patients (4.7%) in Group 1 Vs. 3 patients (4.3%) in Group 2, p=0.277). The P2Y12 inhibition assay level was significantly lower in Group 1, when compared to Group 2 (71.6 Vs 94.8, p=0.027). There was no significant difference in the number of patients achieving a therapeutic value for the P2Y12 inhibition assay value (<194 at our instituion's laboratory) (83.3 in Group 1 Vs. 82.6%, p=0.92). One patient in Group 2 experienced a clinically significant groin hematoma, and one patient in the same group experienced a significant gastrointestinal bleed. No significant hemorrhagic events occured in patients belonging to Group 2. There was also no instance of remote intracerebral hemorrhage or post treatment aneurysm rupture in either group. Conclusion: Lower preoperative P2Y12 assay values from the use of 45 mg twice daily Ticagrelor with 81 mg Aspirin for treatment of UIAs with SAC or FD placement did not result in decreased rates of perioperative stroke or delayed stroke rates within 1 year of surgery when compared to the well established use of Clopidogrel 75 mg and Aspirin 325 mg. Disclosures: T. Mehta: None. K. Masood: None. M. Ghannnam: None. A. Grande: None. R. Tummala: None. B. Jagadeesan: None.